2008
DOI: 10.1080/15560350802081280
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Support Meetings for Youths: Considerations When Referring Young People to 12-Step and Alternative Groups

Abstract: Participation of young people in recovery support meetings is a promising yet largely understudied area. This article reviews the history of youth involvement in meetings, summarizes current research, and discusses issues to consider when making referrals. Professionals may want to research local meetings, help young people structure time before and after meetings, become familiar with group customs, investigate a variety of support groups, interact with support group service structures, develop a list Lora L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Researchers have suggested a need for monitoring adolescents’ attendance and involvement in 12-Step programs and to teach them appropriate meeting etiquette (Cavailoa, Schiff, & Kane-Cavailoa, 1990; Passetti & White, 2010). To better understand the mechanisms by which 12-Step program attendance could be effective, in addition to studying the direct relationship between 12-step attendance and substance use outcomes, researchers have begun to study mediating factors among youth who attend 12-Step programs.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have suggested a need for monitoring adolescents’ attendance and involvement in 12-Step programs and to teach them appropriate meeting etiquette (Cavailoa, Schiff, & Kane-Cavailoa, 1990; Passetti & White, 2010). To better understand the mechanisms by which 12-Step program attendance could be effective, in addition to studying the direct relationship between 12-step attendance and substance use outcomes, researchers have begun to study mediating factors among youth who attend 12-Step programs.…”
Section: Resultsmentioning
confidence: 99%
“…Most group members will be significantly older, with longer substance use histories and different life challenges due to their age 42 . This age difference has also given rise to concerns about safety.…”
Section: Research On Other Recovery Supports For Adolescentsmentioning
confidence: 99%
“…For example, recommendations to attend mutual support groups became increasingly popular following the founding of Alcoholics Anonymous in 1935, and in the mid-twentieth century, the development of the Minnesota Model of treatment relying on 12-step education and meeting attendance 36–38 . Treatment programs have traditionally referred both adults and adolescents to these groups 39–42 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the references of included studies and a number of relevant reviews were screened (i.e., Cavaiola, Schiff, & Kane- Cavaiola, 1990;Deas & Thomas, 2001;Elliott, Orr, Watson, & Jackson, 2005;Passetti, Godley, & Godley, 2012;Passetti & White, 2007;Williams & Chang, 2000;Winters, Botzet, & Fahnhorst, 2011). A list with studies on Narcotics Anonymous found on the Internet was also screened (White, Budnick, & Pickard, 2011).…”
Section: Search Strategymentioning
confidence: 99%